2015
DOI: 10.1177/1535370215600102
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of the anticancer activity of Thai stingless bee (Tetragonula laeviceps) cerumen

Abstract: In vitro and in vivo characterization of the anticancer activity of Thai stingless bee (Tetragonula laeviceps) cerumen AbstractTetragonula laeviceps cerumen was sequentially extracted with 80% (v/v) methanol, dichloromethane, and hexane and also in the reverse order. By the MTT assay and the respective 50% inhibition concentration value, the most active fraction was further purified to apparent homogeneity by bioassay-guided silica gel column chromatography. -Mangostin was identified by highresolution electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
0
22
1
1
Order By: Relevance
“…33 Briefly, CIM-16 plates comprise an upper and a lower chamber separated by a microporous membrane (8 mm pores) with microelectrodes at the underside for impedance-based detection of migrated cells. Initially, 175 mL complete medium and 50 mL serum-free medium were added to the lower and upper chambers of the CIM-16 plate, respectively.…”
Section: Annexin V Stainingmentioning
confidence: 99%
“…33 Briefly, CIM-16 plates comprise an upper and a lower chamber separated by a microporous membrane (8 mm pores) with microelectrodes at the underside for impedance-based detection of migrated cells. Initially, 175 mL complete medium and 50 mL serum-free medium were added to the lower and upper chambers of the CIM-16 plate, respectively.…”
Section: Annexin V Stainingmentioning
confidence: 99%
“…Other advantages include transparent embryos, which permit clear observations in the early stages of development, high fecundity, similar development to that of mammals, and their genetic similarities to humans. 12 In our previous work, we reported the effects of a-mangostin on the embryonic angiogenesis of zebrafish and did not find anti-angiogenic properties of a-mangostin in zebrafish embryos, despite the clear downregulation of the expression of vegfaa and vegfr2 transcripts; 21 however, we did not study other effects on zebrafish embryos than those on angiogenesis. In the present study, we therefore investigated the toxic effects of a-mangostin on embryonic development.…”
Section: Discussionmentioning
confidence: 73%
“…Stingless bee cerumen extracts have also been used as a potential anticancer agent with human breast, lung, liver, stomach and colon cancer cell lines, inducing high cytotoxicity and an apoptotic like cell morphology [ 15 ]. This study also showed that α-mangostin isolated from cerumen induced in vitro cytotoxicity against the above cell lines and in-vivo cytotoxicity against zebrafish embryos [ 15 ].…”
Section: Stingless Bee Cerumenmentioning
confidence: 99%
“…It is important to note that stingless bee products are not restricted to honey, but can involve several products including propolis, beebread, cerumen and bee pollen ( Figure 2 ). Although these are not as common as honey, studies have reported several medicinal properties in those products too [ 14 , 15 , 16 ]. Based on a comparison between the studies on stingless bees and honeybees, a significant gap in research on stingless bee products has been identified compared to the common honeybee products that are well-studied ( Figure 3 ).…”
Section: Introductionmentioning
confidence: 99%